The Effect of Using the Memrise Application on Improving Vocabulary Mastery of Senior High School Students - Widarti, Sinta Putri; Daud, Afrianto; Masyhur (IKIP Siliwangi, 2025)
This research evaluates the effectiveness of using the Memrise application in improving the vocabulary mastery of the second-year students of SMAN 5 Pekanbaru. Employing a pre-experimental design with a pre-test and post-test approach, the research involved a sample of 40 students who underwent vocabulary assessments before and after treatment with the Memrise application. The findings revealed a significant improvement in students' vocabulary mastery, with the average score increasing from 76.80 (pre-test) to 88.90 (post-test). Statistical analysis using a paired sample t-test demonstrated a significance value of <0.001, confirming the positive effect of the Memrise application on vocabulary acquisition. The research highlights Memrise application as an effective digital tool for fostering vocabulary development, offering teachers and students a modern, interactive learning platform. Recommendations are provided for integrating such applications into classroom teaching to enhance language learning outcomes.